2011
DOI: 10.1002/hep.24421
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide microRNA down-regulation as a negative feedback mechanism in the early phases of liver regeneration

Abstract: Liver is one of the few organs that have the capacity to regenerate in response to injury. We carried out genome-wide miRNA microarray studies during liver regeneration in rats after 70% PH at early and mid-time points to more thoroughly understand their role. At 3, 12 and 18 hrs post-PH ~ 40% of the miRNAs tested were up-regulated. Conversely, at 24 hrs post-PH, ~ 70% of miRNAs were down-regulated. Further, we established that the genome-wide down-regulation of miRNA expression at 24 hrs was also correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 31 publications
5
49
0
1
Order By: Relevance
“…Consistent with our observations, previous studies have shown that depletion of miRNA processing enzymes or increased expression of miRNA exonucleases results in widespread decreases in miRNA expression (40)(41)(42)(43). To determine whether SIV infection altered expression of miRNA processing or degrading enzymes, we investigated the expression of three key proteins, AGO2, DICER1, and XRN2, using Western blot analysis.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Consistent with our observations, previous studies have shown that depletion of miRNA processing enzymes or increased expression of miRNA exonucleases results in widespread decreases in miRNA expression (40)(41)(42)(43). To determine whether SIV infection altered expression of miRNA processing or degrading enzymes, we investigated the expression of three key proteins, AGO2, DICER1, and XRN2, using Western blot analysis.…”
Section: Resultssupporting
confidence: 87%
“…MicroRNA targets were also enriched in several cell cycle and immune response pathways. Others have also reported that global downregulation of miRNA is linked to regenerative proliferation in the liver (43) and innate immune responses to pathogens (63). Although the precise effect of miRNA depletion in the GI tract during infection is unclear, these data suggest it might influence the derepression of the innate immune response during infection and cellular regeneration during viral insult.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the Dicer-targeting tumoursuppressive let7, which reduces Dicer protein levels in several cell lines (Tokumaru et al 2008), is downregulated by estrogen treatment (Qian et al 2011), constituting a mechanism for indirect upregulation of Dicer activity by estrogen modulation of miRs. Further, Dicer mRNA is targeted by estrogen-regulated miR-29a, miR-125, let7 and miR-21, and TRBP by let7 (Tokumaru et al 2008, Cochrane et al 2010, Shu et al 2011. From these studies (summarised in Table 2), it is clear that a pattern of regulation is increasingly observed whereby feedback loops involving steroid signalling permit the maintenance of hormoneregulated miR biogenesis at appropriate levels.…”
Section: Estrogen Modulation Of Mir Biogenesismentioning
confidence: 99%